THYROID ABSCESS IN CHILDREN: A CASE SERIES - L, Sook Weih; N, Mazidah; D, Sheena; AZ, Azriyanti; J, Muhammad Yazid; MN, Noor Shafina (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Thyroid gland has low risk of infection due to good vascular supply, lymphatic drainage, high iodine content and enveloping thick fibrous tissue. Thyroid abscess is rarely found in children. We report two cases of thyroid abscess. CASE 1 A 2-month-old girl presented with painless neck swelling for 2 days. There was no history of fever, respiratory or thyroid symptoms. No history of maternal thyroid disease. Examination revealed firm non-tender midline neck swelling measuring 3 cm x 3 cm, normal overlying skin and accompanying cervical lymph nodes. White cells were raised 19.9x109 with increased ESR 97 mm/hr and CRP 6.58 mg/dL [NR <3 mg/dL] with normal thyroid function test (TFT). Thyroid autoantibodies were not performed. Ultrasound revealed well-encapsulated heterogenous mass from left lobe measuring 2.2 cm x 3.9 cm x 4.0 cm causing deviation of trachea medially and left CCA IJV laterally. Aspirated pus yielded Klebsiellae pneumoniae and Enterobacteriae cloacae. TB culture was negative. She received intravenous cloxacillin and cefuroxime and discharged well. CASE 2 A 7-year-old boy presented with one-week history of neck pain, fever and neck swelling. There was no trauma or flulike symptom. Examination revealed 7 cm x 4 cm swelling at anterior, right neck with multiple shotty cervical lymph nodes. TFT was normal with negative inflammatory markers, anti-TPO and anti-TG antibodies. Ultrasound showed heterogenous right lobe measuring 2.8 cm x 3 cm x 5.1 cm with multiple right cervical lymph nodes (largest 0.6 cm). FNAC showed inflammation with perivasculitis, vasculitis with no granuloma or malignant changes. Patient developed purulent discharge after 2 weeks but afebrile. Well-circumscribed swelling was noted at the right anterior neck. Purulent discharge was aspirated with negative culture. Histopathology showed granulation tissue with infiltration by inflammatory cells with micro abscesses. Patient was given co-amoxiclav and discharged well. CONCLUSION Thyroid abscess must be considered although very rare in children. Intensive and appropriate treatment is necessary to prevent recurrence. Anatomical abnormalities like pyriform sinus fistula must be considered especially with atypical organisms or recurrent presentation.